Putting Tradition into Practice: Heritage, Place and Design Proceedings of 5th INTBAU International Annual Event (Lecture Notes in Civil Engineering,, 2018)
This book gathers more than 150 peer-reviewed papers presented at the 5th INTBAU International Annual Event, held in Milan, Italy, in July 2017. The book represents an invaluable and up-to-date international exchange of research, case studies and best practice to confront the challenges of designing places, building cultural landscapes and enabling the development of communities. The papers investigate methodologies of representation, communication and valorization of historic urban landscapes and cultural heritage, monitoring conservation management, cultural issues in heritage assessment, placemaking and local identity enhancement, as well as reconstruction of settlements affected by disasters. With contributions from leading experts, including university researchers, professionals and policy makers, the book addresses all who seek to understand and address the challenges faced in the protection and enhancement of the heritage that has been created.